The Relationship Between Nutritional Behavior and Mental Well-Being Levels of Sports Science Students - Dinç, Ahmet (Progress in Nutrition, 2022)
Purpose: The purpose of this study is to examine the relationship between the nutritional behavior and mental well-being of Igdır University Sports Science Students. Descriptive method was used in the research. The research group of the study has been formed a total of (125 females, 168 males) students schooled at Igdır University Department of Physical Education and Sports College. In order to collect the data of the study, the Attitude Scale Towards Healthy Behavior (ASTHB) developed by Tekkursun Demir and Cicioglu (2019) and the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) scale adapted to Turkish by Keldal (2015) were used. The Attitude Scale for Healthy Nutrition Behavior and the Warwick-Edinburgh Mental Well-Being Scale is a 5-point Likert-type scale. SPSS-24 package program was used for data analysis. The skewness and kurtosis values have been examined to find out whether the data had a normal distribution. As a result, it has been determined that the data had a normal distribution. Descriptive statistical analysis and correlation analysis have been used in the analysis of the data. Considering the research findings, it has been seen that the nutrition and mental well-being levels of sports science students were high. As a result of the correlation analysis, it has been determined that there is a statistically significant positive correlation between information about nutrition and positive nutrition dimension and mental well-being.